A global financial history of oil crises - Altamura, Carlo Edoardo, author. Link Link
1 online resource (150 pages)
Keywords: In this book, Altamura analyses the oil shocks of 1973 and 1979, considering their impact on the world economy and subsequent reactions to the global instability.In terms of actors, the focus is on how international organisations such as the IMF, World Bank and OECD responded to the crisis, as well as the behaviour of commercial banks and central banks and of countries in the Global South. Altamura draws on newly available archival material from private financial institutions to paint a full picture of a rapidly changing world which paved the way for stagflation and interdependency.This monograph will be illuminating reading for economic and financial historians, plus scholars looking at energy history, the Cold War in a global context, the New International Economic Order and the political economy of the 1970s.